INNOVATIVE APPROACHES TO MANAGING EDUCATIONAL INSTITUTIONS IN THE CONTEXT OF DIGITALIZATION (Web of Teachers: Inderscience Research, 2024)
The process of digitalization is now occupying an important place in all spheres of society, including education. The use of innovative approaches in the management of educational institutions contributes to improving the quality of education, ensuring effective management and improving the educational process. Innovative approaches to managing educational institutions in the context of digitalization bring many new opportunities and methods.